Atafona e Moinho Henkel. Nova Hartz. RS: estudo sobre o patrimônio material e imaterial - Oliveira, Kátia Ferreira de (2009)
In the south of the American continent, there are thousands of years, the people of the Tropical forest cultivate the brave manioc and, starting from her, produce the flour and other derivates, essential foods of your diet. In Nova Hartz, valley of the Sinos river region, before the footwear industry take great part in the economy, the production of manioc flour was the main economic activity. What was known as the atafonas produced flour to be commercialized in and outside Brazil. They contributed to the economical development of the German Colony of São Leopoldo and also of Rio Grande do Sul. Nowadays, these familiar agro-industries are in their way of disappearing in Nova Hartz, as well as in the region. It s inside this context that the Henkel family s atafona and mill are. This atafona, apart from the others, got to the 21st century producing manioc flour, the main income source of the family. The mill, on the other hand, had its activities finished by the second half of the 20th century. At first, the mill produced corn flour for the family s own consumption, and they also sold the milling service to neighbors. Later, in the period that the atafona produced manioc scrapings to be incorporated to wheat flour, it was used to grind it and it finished its activities peeling rice. These work places, both residences of the family, the kitchen and dining room, the system of energy generation constituted of dam, canal and water wheels, the manioc culture techniques, the way and the machinery used to make the flour are material and non-material testimonies of part of the local and regional history. This research has as goal, through the study of this patrimony, to attribute to the Henkel s Atafona and Mill historic site values that can contribute with his recognition and preservation. These values can also serve as basis to the historic site's reutilization projects that contribute to his maintenance. From the classification of all these goods and industrial heritage, drawing on the Charter of Nizhny Tagil, prepared by the International Commission for the Conservation of Industrial Heritage - TICCIH this study was structured to be able to clarify their core values. Through various authors with varied backgrounds, work documentation, writing and iconographic and field surveys with photographic records were combined history and memory, art, architecture, archeology, anthropology, agronomy, economy, among other disciplines.